2010
DOI: 10.1021/cm903260f
|View full text |Cite
|
Sign up to set email alerts
|

Highly Visible Light Active TiO2−xNx Heterojunction Photocatalysts

Abstract: Nitrogen doped anatase-rutile heterojunctions are successfully synthesized through an ethylenediaminetetraacetic acid (EDTA) modified sol−gel process. An FT-IR study of EDTA modified TiO2 gel confirms the existence of an ionic intermediate (as indicated by a Δν value of 233 cm−1). Differential scanning calorimetry (DSC), X-ray diffraction (XRD), and Raman spectroscopy are employed to study the phase evolution, phase purity, and crystallite size of samples. Formations of O−Ti−N and N−Ti−N bonds in calcined samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
212
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 278 publications
(232 citation statements)
references
References 61 publications
16
212
1
3
Order By: Relevance
“…Induced low temperature rutile formation in the presence of nitrogen is contradictory to previous reports by this group [41]. It has been previously observed that using urea as a nitrogen source alters the condensation pathway, extending the temperature at which rutile forms [42]. However, the current study shows that 1,3-diaminopropane stabilises titanium tetraisopropoxide as a monomer which will contribute to the low temperature formation of rutile.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Induced low temperature rutile formation in the presence of nitrogen is contradictory to previous reports by this group [41]. It has been previously observed that using urea as a nitrogen source alters the condensation pathway, extending the temperature at which rutile forms [42]. However, the current study shows that 1,3-diaminopropane stabilises titanium tetraisopropoxide as a monomer which will contribute to the low temperature formation of rutile.…”
Section: Discussioncontrasting
confidence: 99%
“…6, show peaks with binding energies of ∼401 eV which is higher than the typical N1s value but can be attributed to the binding of the 1s electron of N in the environment of O-Ti-N in lattice N-doped TiO 2 . The change in binding energy is due to the N substituting for oxygen in the O-Ti-O structure and the electron density around nitrogen becoming reduced compared to that of a TiN crystal, due to the presence of the oxygen atom [42]. This observation is consistent with literature on the oxidation of TiN surfaces [44].…”
Section: X-ray Photoelectron Spectroscopysupporting
confidence: 90%
See 2 more Smart Citations
“…In all the spectra, the strong and broad band below 1000 cm -1 is assigned to the combined bands of Ti-O-Ti, Fe-O-Ti, S-O-Ti and O-Ti-C crystal vibrations, 24 and the absorption bands at 1628 cm -1 and around 3500 cm -1 are due to -OH bending and stretching vibrations respectively as a result of absorbed water molecules. For the C/S-doped Ti-O 2 and Fe 3+ /C/S-doped TiO 2 photocatalysts (Figure 2b, 2c, 2d and 2e), the peak located at 1065 cm -1 may be attributed to bidentate sulphate ions (SO 4 2-) co-ordinated to metal ions such as T 4+ .…”
Section: Ftir Analysismentioning
confidence: 98%